A new species of the subterranean millipede genus Antrokoreana Verhoeff, 1938 from the Nanatsuoguchi Mine, central Honshu, Japan, and insights into the phylogenetic position of Antrokoreana (Diplopoda, Julida, Nemasomatidae) - Kato, Taiga; Umemura, Shinya; Nakano, Takafumi (Zootaxa, 2022)
A new species of the subterranean millipede genus Antrokoreana Verhoeff, 1938, A. asuwaensis sp. nov., from the Nanatsuoguchi Mine in central Honshu, Japan, is described based on both sexes. The new species is clearly distinguished from all congeners by the distally expanded coxal process of its anterior gonopods. Characteristics of the antennomere VII, mandibular pectinate lamellae, and flagella of anterior gonopods provide insight into the diagnostic features of Antrokoreana. Nuclear 28S ribosomal RNA as well as mitochondrial cytochrome c oxidase subunit I and 16S ribosomal RNA sequences of the new species are provided, and its phylogenetic position is preliminary estimated based on the 28S and 16S rRNA sequences. The obtained phylogenies show non-monophyly of the three genera of Nemasomatidae suggesting the possibility that Antrokoreana forms a clade that is distinct from that of the other nemasomatid genera.